East Timor : The Price of Freedom - Taylor, John G. (London Zed Books, 1999)
"In this updated and much expanded edition of his book, Indonesia's Forgotten War: The Hidden History of East Timor, John Taylor tells in detail the story of what happened to this island people following President Suharto's downfall in the wake of the Asian economic crisis. The new Indonesian government conceded the right of the United Nations to organise the long delayed referendum giving the East Timorese a choice between continued association with Indonesia or independence. At the very moment the historic vote was being counted, however, armed gangs organised by elements of the Indonesian military plunged the island into an orgy of killing, burning and forced flight. An appalled world witnessed their bloody defiance of the people's will and of the international community. John Taylor analyses the world' reaction to this new genocide of the East Timorese people, the belated despatch of a peacekeeping force, and the prospects of independence."--Jacket.
Include Chronology, Glossary, Bibliography and Index
Keywords: Politics and government -- Timor-Leste